a ) 42 x 99 + 42
= 42 x 99 + 42 x 1
= 42 x ( 99 + 1 )
= 42 x 100
= 4200
b ) 28 : 4 - 12 : 4
= ( 28 - 12 ) : 4
= 16 : 4
= 4
a 42 x {99+1}
42x100=4200
b {28-12}/4
16/4
4
a) 42x99+42 = 42 x ( 99 + 1 ) = 42x100 = 4200
b) 28:4 - 12: 4 = 28 x 1/4 - 12x1/4 = 1/4 x ( 28 - 12 ) = 1/4 x 16 =4
a) 42x99+42
=42x99+42x1
=42x(99+1)
=42x100
=4200
b)28:4-12:4
=(28-12):4
=16:4
=4
a) 42x99+42
=42x99+42x1
=42x(99+1)
=42x100
=4200
b) 28:4-12:4
=(28-12):4
=16:4
=4
a:42x99+42
=42x(99+1)
=42x100
=4200
b: 28:4-12:4
=(28-12):4
=16:4
=4
k mik nha
a) 42 x 99 + 42
42 x 99 + 42 x 1
42 x ( 99 + 1 )
42 x 100
4200
b) 28 : 4 - 12 : 4
( 28 - 12 ) : 4
16 : 4
4